THE ECOTOURISM MANAGEMENT STRATEGY BASED ON THE INFLUENCED FACTOR TOWARDS VISITORSâ DECISION TO VISIT AND SATISFACTION AT EKOWISATA KAMPUNG BLEKOK - Rizka Estiningtyas, Nabilah
Kampung Blekok is a mangrove and water bird-based conservation area that officially becoming an ecotourism in 2019. The average number of visits each day in 2022 was 39 visitors. On the other hand, the area carrying capacity was recorded as 648 visitors each day. The difference between carrying capacity and factual data shows that optimization efforts are needed to increase visitor numbers within reasonable limits, considering tourism activities play an essential role in the economic movement. The manager's ability to understand how visitors behave can support these efforts. The primary keys to understanding visitor behavior are satisfaction and experience gained in the location. These two can be achieved by understanding the visitors’ motivation as an internal factor and the destination readiness as an external factor that leads to the visiting decisions. Understanding visitor behavior and destination readiness allows to used as a basic for formulating management improvement strategy. Therefore, this research aims to 1) Identify the ongoing management conditions through content analysis modified of the assessment of natural tourism attraction objects and balanced scorecard; 2) Analyze factors influencing visitors' decision to visit and satisfaction through structural equation modeling – partial least square and importance-performance map analysis; 3) Determine management improvement strategies at Ekowisata Kampung Blekok through strengths, weaknesses, opportunities, and threats, we used a quantitative strategic planning matrix analysis. The result shows that the ongoing management performance stood at 47.30%. The absence of planning and targeting reflects ineffective management. Furthermore, financial and communication problems also reflect ineffective management. On the other hand, Ekowisata Kampung Blekok has potential and worthy development with a feasibility index value of 74.44%. The tourist visiting decision is influenced by service quality (tangible, responsiveness, reliability, assurance, empathy, eco-activities, eco-education, eco-practices) and marketing mix (product, price, place, physical evidence, promotion, and process). Besides, visitor satisfaction is influenced by service quality dan visiting decision. The Three priority strategies for improving management are 1) strengthening communication and institutional of kelompok sadar wisata; 2) carrying out conservation and environmental-based activities 3) increasing awareness, skills, and capacity of kelompok sadar wisata